(untitled) (Educational Knowledge, 2023)
This work seeks to comprehend the significance of education in combating aporophobia in society, acknowledging that learning can occur within the framework of respect for human rights and by addressing discrimination against marginalized individuals, particularly those in poverty. Employing a documentary research methodology with critical and hermeneutic analysis, the study concludes that cooperation between government and society is essential for developing educational policies that elucidate human dignity and equality. Such policies, embraced both nationally and internationally, contribute to social justice by fostering coexistence and recognizing sociocultural, ideological, and political diversity. Schools are pivotal in preventing the proliferation of the phobia discussed, thereby mitigating its impact on individuals.